Long‐Term Follow‐up of the PADI Trial: Percutaneous Transluminal Angioplasty Versus Drug‐Eluting Stents for Infrapopliteal Lesions in Critical Limb Ischemia. Issue 4 (April 2017) - Spreen, Marlon I.; Martens, Jasper M.; Knippenberg, Bob; van Dijk, Lukas C.; de Vries, Jean‐Paul P. M.; Vos, Jan Albert; de Borst, Gert Jan; Vonken, Evert‐Jan P. A.; Bijlstra, Okker D.; Wever, Jan J.; Statius van Eps, Randolph G.; Mali, Willem P. Th. M.; et al.
Abstract : Background: Clinical outcomes reported after treatment of infrapopliteal lesions with drug‐eluting stents (DESs) have been more favorable compared with percutaneous transluminal angioplasty with a bailout bare metal stent (PTA‐BMS) through midterm follow‐up in patients with critical limb ischemia. In the present study, long‐term results of treatment of infrapopliteal lesions with DESs are presented. Methods and Results: Adults with critical limb ischemia (Rutherford category ≥4) and infrapopliteal lesions were randomized to receive PTA‐BMS or DESs with paclitaxel. Long‐term follow‐up consisted of annual assessments up to 5 years after treatment or until a clinical end point was reached. Clinical end points were major amputation (above ankle level), infrapopliteal surgical or endovascular reintervention, and death. Preserved primary patency (≤50% restenosis) of treated lesions was an additional morphological end point, assessed by duplex sonography. In total, 74 limbs (73 patients) were treated with DESs and 66 limbs (64 patients) were treated with PTA‐BMS. The estimated 5‐year major amputation rate was lower in the DES arm (19.3% versus 34.0% for PTA‐BMS; P =0.091). The 5‐year rates of amputation‐ and event‐free survival (survival free from major amputation or reintervention) were significantly higher in the DES arm compared with PTA‐BMS (31.8% versus 20.4%, P =0.043; and 26.2% versus 15.3%, P =0.041, respectively). Survival rates were comparable. The limited available morphological results showed higher preserved patency rates after DESs than after PTA‐BMS at 1, 3, and 4 years of follow‐up. Conclusions: Both clinical and morphological long‐term results after treatment of infrapopliteal lesions in patients with critical limb ischemia are improved with DES compared with PTA‐BMS. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00471289.